Catamenial Pneumothorax in a Patient with Adenomyosis: A Case Report on a Successful Multidisciplinary Approach with Pleurodesis and Hormonal Therapy - Vanny Syafitri; Suyastri (HM Publisher, 2025)
Background: Catamenial pneumothorax, a rare manifestation of thoracic endometriosis syndrome (TES), presents a significant diagnostic and therapeutic challenge. It is characterized by recurrent spontaneous pneumothorax occurring in temporal relation to menstruation in women of reproductive age. The underlying pathophysiology is complex, often involving the ectopic presence of endometrial tissue within the thoracic cavity. Coexisting pelvic pathologies, such as adenomyosis, may be associated, further complicating the clinical picture. Case presentation: We present the case of a 38-year-old woman with a four-month history of recurrent, right-sided pneumothorax, with symptoms consistently commencing 24 to 48 hours prior to the onset of her menstrual cycle. Initial investigations, including high-resolution computed tomography of the thorax performed between menstrual cycles and microbiological analysis for tuberculosis, were unremarkable. The diagnosis of catamenial pneumothorax was established based on the distinct cyclical pattern of her symptoms. A subsequent gynecological evaluation, prompted by a history of secondary dysmenorrhea and menorrhagia, revealed uterine adenomyosis via transvaginal ultrasonography. The patient was managed through a collaborative, multidisciplinary approach involving pulmonology, thoracic surgery, and gynecology. Treatment consisted of chemical pleurodesis with doxycycline, administered via a chest tube, followed by continuous hormonal suppression therapy with oral progestin (2 mg/day). Conclusion: This case highlights the critical importance of maintaining a high index of suspicion for catamenial pneumothorax in women of reproductive age presenting with recurrent pneumothorax. A successful outcome was achieved through a coordinated, multidisciplinary strategy combining definitive pleural symphysis via pleurodesis with systemic hormonal therapy to suppress the underlying endometriotic process. This dual approach effectively prevented pneumothorax recurrence over a 12-month follow-up period, underscoring its efficacy in managing this complex condition.